PEMODELAN NUMERIK ALIRAN FLUIDA PADA TIANG SILINDER DENGAN METODE BEDA HINGGA - Anasiru, Triyanti; Setiyawan, Setiyawan (MEKTEK, 2010)
Fluid flow in nature represent stream three dimension. For example, coordinate of Cartesian of streamrepresent variable of component instruct X, Y and Z. Equation of the Stream developed from ConservationLaws Of Mass and Punish Newton II, later recognized with equation of continuity and equation of motionmean of Navier Stokes.This Writing aim to to get model of numeric for case of simple fluid flow and the fluid flow which through ofpillar cylinder by using method different till. And also make analysis to result resolving of the problems.In test model program made to be conducted by using uniform stream for the ideal fluid by discrete 152 X 52Grid. This model tried to be made ideal fluid (unviscous, incompressible and unsteady). This model intendedto can see stability use of different model till in resolving of case of hydrodynamics and fluid dynamicsAnalyze performed within this writing for example every price early to model fluid case of uniform stream byusing program of Matlab 7.1 giving different result for the same case depend on initially condition. Fromresult analyze the way of handling of boundary condition very influence result of calculation. In general thecorrectness mount if order correctness of different operator till used mount